SmartPave: An Advanced IoT-Based System for Real-Time Pothole Detection, Tracking, and Maintenance - Bej, Sahel; Roy, Swarnava; Daw, Debjit; Paul, Alok; Saha, Shubhojit; Maity, Satyabrata; Ghosh, Nimisha (2023 International Conference in Advances in Power, Signal, and Information Technology (APSIT), 2023)
In recent times, the use of roadways as a mode of transportation has seen a surge in global popularity. Maintaining well-structured roads is crucial to economic growth and social development, especially in developing countries like India. However, the maintenance of roads is becoming an emerging concern due to poor road conditions and potholes. Potholes are a major road infrastructure problem, causing vehicle damage and posing a risk to road safety. This research proposes an IoT-based pothole-tracking system that uses a deep-learning based object detection mechanism and ultrasonic sensors to detect and track potholes on roads. It aims to contribute to developing effective solutions for improving road safety and maintenance, while also addressing its practicality and cost considerations for its implementation. The results of the proposed work on a dataset of potholes demonstrate its effectiveness in detecting potholes.